2010
DOI: 10.1093/occmed/kqq164
|View full text |Cite
|
Sign up to set email alerts
|

Improving estimates of specialist-diagnosed, work-related respiratory and skin disease

Abstract: We have provided a significant improvement in the surveillance-based methodology used to estimate the number of cases of WRIH captured by THOR and hence enabled more accurate estimations of GB incidence rates for clinical specialist-reported WRIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Recent analysis of THOR data has been undertaken to estimate the number of additional cases not captured in 2005–2007, focusing on respiratory and skin diagnoses 21. It was found that 98% of eligible physicians had been approached to report to EPIDERM, and that dermatologists’ participation rates were high (65%); overall it was estimated that 62% cases were captured by EPIDERM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of THOR data has been undertaken to estimate the number of additional cases not captured in 2005–2007, focusing on respiratory and skin diagnoses 21. It was found that 98% of eligible physicians had been approached to report to EPIDERM, and that dermatologists’ participation rates were high (65%); overall it was estimated that 62% cases were captured by EPIDERM.…”
Section: Discussionmentioning
confidence: 99%
“…Annual average incidence rates (per 100 000 persons employed per year) by industry and occupation were calculated for the period 1996 to 2013 (information on industry was not routinely collected during the pilot period). The numerator was the estimated case counts, adjusted to take into account the proportion of UK physicians participating in EPIDERM and the proportion of physicians responding during their reporting month(s) . The denominator was the number of persons employed (1996‐2013) according to the LFS.…”
Section: Methodsmentioning
confidence: 99%
“…The SWORD methodology has been described previously 18 19. Briefly, respiratory physicians return reports of work-related respiratory disease to SWORD specifying the suspected causal agent(s).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection began in 1993 as part of the Occupational Disease Intelligence Network, and it has been part of The Health and Occupation Research Network since 2002 18. Approximately 70% of the eligible respiratory physicians were registered as SWORD reporters in 2005 19. Since 1999, the incidence of asthma reported to SWORD has been declining 20 21…”
Section: Introductionmentioning
confidence: 99%